Linear quadratic regulator controllers for regulation of the dc-bus voltage in a hybrid energy system: modeling, design and experimental validation - Abdullah, Majid A. (Elsevier Ltd, 2022)
In this paper, linear quadratic regulator (LQR) controllers for effective operation of a hybrid energy system consisting of ultracapacitor energy storage and wind energy system have been designed and implemented. The control objective is to regulate the dc-bus voltage to a target level while extracting the maximum power from the available wind. The dc-bus voltage regulation is achieved by controlling the charging and discharging of the ultracapacitor through a bidirectional converter, and tracking the maximum power points (MPPs) is achieved by controlling a boost converter interfacing the wind turbine with the dc-bus. In addition, a boost converter-based wind turbine emulator to behavior similar to a real wind generator has been developed for testing the proposed controllers. The performance of the proposed energy system incorporating the LQR controllers has been tested under several scenarios (both in simulations and experiments), and the results presented. The simulation tests were conducted in the environment of MATLAB/Simulink, and the experimental tests implemented based on low-cost Digital Signal Processor (DSP) TMS320F2812 eZdsp board. The simulation and experimental results demonstrate their consistency and the capability of the proposed LQR controllers to (1) track the reference voltages and currents, and (2) swiftly recover the nominal operating condition of the system at all conditions including any variation in wind speed or load demand.